Clouds and Seasonality on Terrestrial Planets with Varying Rotation Rates - Daniel A. Williams; Xuan Ji; Paul Corlies; Juan M. Lora (The Astrophysical Journal, 2024)
Using an idealized climate model incorporating seasonal forcing, we investigate the impact of rotation rate on the abundance of clouds on an Earth-like aquaplanet, and the resulting impacts upon albedo and seasonality. We show that the cloud distribution varies significantly with season, depending strongly on the rotation rate, and is well explained by the large-scale circulation and atmospheric state. Planetary albedo displays nonmonotonic behavior with rotation rate, peaking at around 1/2Ω _E . Clouds reduce the surface temperature and total precipitation relative to simulations without clouds at all rotation rates, and reduce the dependence of total precipitation on rotation rate, causing nonmonotonic behavior and a local maximum around 1/8Ω _E ; these effects are related to the impacts of clouds on the net atmospheric and surface radiative energy budgets. Clouds also affect the seasonality. The influence of clouds on the extent of the winter Hadley cell and the intertropical convergence zone is relatively minor at slow rotation rates (<1/8Ω _E ), but becomes more pronounced at intermediate rotation rates, where clouds decrease their maximum latitudes. The timing of seasonal transitions varies with rotation rate, and the addition of clouds reduces the seasonal phase lag.